The degree to which students with visual impairments in Jordanian public schools use their assistive technology to study subjects in inclusive schools from their point of view - Ali Alhabahbe, Fadia; Subhi Alhadidi , Muna (Dirasat: Human and Social Sciences, 2022)
The current study aims to identify the degree to which students with visual disabilities in Jordanian public schools use their own educational technologies to study subjects in inclusive schools from their point of view in light of some variables represented by gender, degree of disability, and school stage. The sample consisted of (349) male and female students with visual impairment who were selected by a stratified random method. To achieve the objectives of the study, a scale of the degree of use of educational technologies was built, divided into three dimensions: electronic Braille display screens, electronic reading aids, and a magnifying screen. The psychometric properties of the scale were verified. The results showed that the degree of using educational technologies among students with visual disabilities in inclusive Jordanian public schools was low, with an arithmetic mean of the total score (1.80). They also revealed that there were no statistically significant differences at the significance level (α = 0.05) in the level of students' use of educational technologies according to grade and degree of disability. The results also revealed a statistically significant difference according to the gender variable in favor of males